Angiotensin converting enzyme inhibitors and angiotensin receptor blockers impact on the gut microbiome: a systematic review - Wang, Elisabeth M.; Shremo Msdi, Abdulwhab; Quach, Vy N.; Nguyen, Selena Q.; Quach, Emily; Jo, Jinhee; Eubank, Taryn A.; Garey, Kevin W.; Rosario, Natalie (Frontiers in Endocrinology, 2025)
BackgroundInhibition of the renin–angiotensin system (RAS) may influence gut microbial composition and blood pressure, yet current evidence remains limited. This review examines how angiotensin-converting enzyme inhibitors (ACEis) and angiotensin receptor blockers (ARBs) modify gut microbiome composition, function, and blood pressure regulation.MethodsWe conducted a systematic search of MEDLINE and EMBASE from inception to September 2025 using terms including “human,” “rat,” “angiotensin converting enzyme inhibitor,” “angiotensin receptor blocker,” and “gut microbiome.” Eligible studies were required to report changes in microbiome diversity, bacterial composition, or short-chain fatty acids (SCFAs) associated with ACEi/ARB treatment across animal or human models. Data extraction and risk of bias assessments were performed independently by multiple reviewers.ResultsAfter deduplication, 642 retrieved articles were filtered and nine met inclusion criteria (eight in rodent models, one human study). ACEi/ARB administration in animals was associated with increased microbial diversity, restoration of intestinal oxygen balance, and enrichment of SCFA-producing anaerobic genera such as Bifidobacterium, Bacteroides, Blautia, and Akkermansia. In the human study, ACEi/ARB use did not significantly alter microbial diversity, but decreased populations of facultative aerobic pathogens including Staphylococcus and Enterobacterales. Functionally, prolonged RAS inhibition elevated levels of acetate, propionate, and butyrate, and enhanced gut barrier integrity while attenuating inflammatory signaling. The human study was found to have a moderate risk of bias.ConclusionsACEi and ARB therapies appear to reshape gut microbiome structure and metabolic function, promoting SCFA-producer expansion, improved gut barrier integrity, and modulation of microbial taxa linked to inflammation and hypertension. However, human data is limited, and further transitional research is needed to confirm these findings.